Rätt till materiell prövning? - En analys av det civilprocessrättsliga medgivandets förhållande till enskildas rätt till ett effektivt domstolsskydd mot bakgrund av Braathens-fallet - Ask,Emma (2024)
In Swedish civil procedure, the respondent can choose to either concede or contest the plaintiff's claim. If the plaintiff's claim is conceded, the court must, in a case amenable to out-of-court settlements, give judgment based on the respondent’s concession without examining the grounds for the claim. This follows from the dispositionsprincipen (principle of disposit-ion): a fundamental principle that the court may not give judgment on matters beyond that which the parties have brought forward. Although the plaintiff’s claim may be conceded, the respondent does not have to recognise the grounds for the claim. This has led to situations where the respon-dent concedes to a claim but simultaneously opposes the grounds of the claim expressively. In the event that judgment is given in relation to a con-cession but the grounds of the claim have been expressly opposed by the respondent, the question that arises is whether such a judgment is enough to satisfy the plaintiff's right to effective judicial protection. This paper aims to examine Swedish civil procedural law regarding concession and how this relates to the individual's right to effective judicial protection. The right to effective judicial protection is enshrined in EU law as well as the ECHR. This paper will mainly examine national laws, whilst also considering aspects of EU and European law. To investigate the quest-ions of this paper, the “legal-dogmatic method” is used to determine and analyse established law. The legal issue this paper addresses first arose in the Braathens case, which was essentially a case of discrimination. The Court of Justice of the European Union (CJEU) gave a preliminary ruling stating that it is not in accordance with EU law to give judgments without judicial review just because the respondent has agreed to pay compensation for discrimination without conceding that the plaintiff has been discriminated against. The CJEU imposed an obligation on national courts to examine the merits of the claim at the request of the plaintiff, even though it had been conceded. The obligation imposed by the CJEU on national courts is not compatible with the principle of disposition. The Braathens case also raises numerous uncertainties, such as whether national courts are precluded from pronouncing judgment after the respondent’s concession in cases other than discriminatory ones. There are some alternative approaches as to how national courts could deal with the issue raised in the Braathens case. In my view, none of the possible approaches explored in this paper provides a sustainable solution that safeguards the structure of national civil procedur-al law whilst also considering the individual’s right to effective judicial protection. This paper shows that several issues arise from the CJEU's de-cision in the Braathens case that should be addressed in a legislative pro-cess to maintain a coherent application of the law.
Keywords: civilrätt; EU-rätt; processrätt; dispositionsprincipen